2012
DOI: 10.1111/j.1582-4934.2011.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction proteins expression and modulation in immune cells and multiple sclerosis

Abstract: The tight junction proteins (TJPs) are major determinants of endothelial cells comprising physiological vascular barriers such as the blood–brain barrier, but little is known about their expression and role in immune cells. In this study we assessed TJP expression in human leukocyte subsets, their induction by immune activation and modulation associated with autoimmune disease states and therapies. A consistent expression of TJP complexes was detected in peripheral blood leukocytes (PBLs), predominantly in B a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 78 publications
4
44
0
Order By: Relevance
“…The present work extends the report of Mandel et al [20, 21], which noted an increase in CLN-5 + leukocytes in blood from MS patients who experienced disease relapse. Our findings corroborated the presence of CLN-5 + leukocytes in blood during EAE, an animal model of MS [5456], and further demonstrated their appearance in the CNS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present work extends the report of Mandel et al [20, 21], which noted an increase in CLN-5 + leukocytes in blood from MS patients who experienced disease relapse. Our findings corroborated the presence of CLN-5 + leukocytes in blood during EAE, an animal model of MS [5456], and further demonstrated their appearance in the CNS.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, Mandel et al [20] observed TJ proteins of the claudin (CLN) family—notably CLN-1 (CLN-1 + ) and CLN-5 (CLN-5 + )—in peripheral blood leukocytes (PBLs) from both healthy individuals and those affected with the neuroinflammatory condition multiple sclerosis (MS). They further noted an increase in CLN-1 and CLN-5 protein expression by PBLs from MS patients experiencing disease relapse, compared to healthy controls or patients in remission.…”
Section: Introductionmentioning
confidence: 99%
“…30 Consistent expression of tight junction proteins was also reported in human leucocytes, primarily in lymphocytes and monocytes, and they were suggested to play a role in immune activity and autoimmunity. 31 Tight junction proteins (eg, CLDN19) were also proposed among possible biomarkers for refractory lupus nephritis. 32 SGK223 (http:// www.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR analyses were performed using the FastStart Universal SYBR Green Master-Rox (Roche) on the AB 7300 sequence detection system in duplicates. The ubiquitin-conjugating enzyme E2 D2 ( UBE2D2 ) gene was used as a reference gene as in previous and the present studies its levels were unaffected by IFN-β [38]. Relative quantification of mRNA expression was calculated using the comparative CT method and is shown as fold change of expression (2 −ΔΔ C T ) [39].…”
Section: Methodsmentioning
confidence: 99%